Economic resources and the first child in Italy: A focus on income and job stability - Elisabetta Santarelli (Demographic Research, 2011)
At the turn of the twentieth century Italy registered a lowest-low fertility level, i.e., a total fertility rate of 1.26 children per woman in 2000. In this paper we investigate whether and how in that period economic resources and, in particular, income and job stability were linked with couples' decisions to enter parenthood. With this aim, we use data from ECHP and carry out a longitudinal analysis on a sample of childless married couples to study the transition to their first child. Results show that the couples' employment arrangement played some role in first child rates, with the single earner arrangement experiencing the highest first birth rates. We also find that employed women with labour income have much lower first birth rates than non-working women, while no evidence is found for male earnings and other sources of income. As concerns job instability, we find evidence that it was not significantly linked with the transition to first time parenthood during the investigated period.